MODEL KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN KOMPETENSI PEDAGOGIK DAN KOMPETENSI PROFESIONAL GURU PENDIDIKAN AGAMA ISLAM DI SMPN 03 JABUNG MALANG - Masruroh Masruroh; Rosichin Mansur; Dwi Fitri Wiyono (Vicratina : Jurnal Ilmiah Keagamaan, 2022)
A school principal is the highest leader in educational institutions who are desperately needed to bring the institution to the goals that have been set, one of which is the formation of students who are knowledgeable and have good morals. To realize one of these goals, the role of a teacher is very significant, therefore it takes teachers who have superior competence both scientifically (professional competence) and competence in the learning process (pedagogic competence), and principal leadership has a major role in efforts to improve these competencies. In this study, the researcher tries The principal who is considered meritorious presents a central figure, namely the principal who is considered meritorious to increasing teacher competence at SMPN 03 Jabung Malang. With the application of a democratic leadership model, using participatory strategies, and forms of pedagogic and professional competencies that have been applied by PAI teachers at SMPN 03 Jabung Malang are; (a) using various learning methods, b) creating a conducive classroom climate, (c) using learning media that pays attention to the principle of efficiency.